Rhodium(I)-a-Phenylvinylfluorenyl Complexes: Synthesis, Characterization, and Evaluation as Initiators in the Stereospecific Polymerization of Phenylacetylene - Tan, N.; Simpson, Peter; Nealon, G.; Sobolev, A.; Raiteri, Paolo; Massi, Massimiliano; Ogden, Mark; Lowe, Andrew (Wiley - V C H Verlag GmbH, 2019)
The synthesis, characterization and use, as initiators for phenylacetylene polymerizations, of three new rhodium(I)-vinyl complexes containing fluorenyl functionality with fluorine-functionalized phosphine ligands is described. Rh(nbd)(CPh=CFlu)P(4-FC6H4)3, Rh(nbd)(CPh=CFlu)P(4-CF3C6H4)3, and Rh(nbd)(CPh=CFlu)P[3,5-(CF3)2C6H3]3 (nbd: 2,5-norbornadiene; Flu: fluorenyl) were prepared and isolated as discrete, orange compounds and were readily recrystallized yielding X-ray quality crystals. All complexes were characterized by a combination of 1H, 31P, 19F, 103Rh NMR spectroscopy and 2D 31P-103Rh/31P-103Rh{103Rh} heteronuclear multiple-quantum correlation (HMQC) experiments, elemental analysis, and single-crystal X-ray analysis. The complexes were active as initiators in the co-ordination insertion polymerization of phenylacetylene, with initiation efficiencies spanning the range 13–56 %, and yielded polyphenylacetylenes of low dispersity (Ð = Mw/Mn) with high cis-transoidal stereoregularity.